Association between circadian syndrome and MASLD risk: evidence from a large cross-sectional study - Jihan Sun; Shuqi Mao; Caide Lu (BMC Gastroenterology)
Abstract Background Metabolic dysfunction-associated steatotic liver disease (MASLD) is a prevalent chronic liver condition closely associated with metabolic syndrome and linked to circadian disruptions. Circadian Syndrome (CircS), a constellation of metabolic and circadian dysregulations, has emerged as a risk factor for metabolic disorders. This study aims to examine the association between CircS and MASLD and to evaluate the potential relevance of CircS in identifying individuals at elevated MASLD risk. Methods Data from 2,288 participants in the 2017–2018 U.S. National Health and Nutrition Examination Survey (NHANES) cycle were analyzed. Weighted logistic regression models were used to assess the overall association between CircS and MASLD. Restricted cubic spline (RCS) analyses were applied to evaluate the dose–response relationship. Subgroup analyses were conducted to explore potential effect modifiers underlying the CircS-MASLD association. Results A significant association between CircS and MASLD was observed. Application of weighted logistic regression revealed that individuals with CircS had increased odds of MASLD (adjusted OR = 4.123, 95% CI: 2.489–6.832, P = 0.001) after adjusting for demographic, lifestyle, and metabolic covariates. The association was consistent across demographic subgroups, with a linear trend showing higher CircS scores correlating with increased MASLD risk. Conclusion CircS is significantly associated with MASLD and may have potential implications for early risk identification and targeted intervention. However, its clinical utility requires further validation in prospective studies before integration into routine practice.